Caries preventive interventions in community-dwelling elders: a systematic review/ Eleena Mohd Yusof, May Lei Mei and Angus Walls - Mohd Yusof, Eleena; May, Lei Mei; Walls, Angus (Faculty of Dentistry, 2018)
To conduct a systematic review of identifying the clinical efficacy of caries preventive interventions in community-dwelling elders. As the human lifespan increases, the elders are known to retain their teeth for longer. Therefore, the need to uncover effective ways of preventing caries among this age group is relevant. A search was conducted using four databases: Cochrane, MEDLINE, EMBASE and Web of Science using the keywords (caries OR demineralization) AND prevention AND (adult OR aged). The titles and abstracts were initially screened for the use of caries prevention interventions. Studies were excluded based on the predetermined criteria. The full texts of the remaining studies were then evaluated. Of 6952 articles identified from the search, fifty full texts were evaluated. Finally, ten studies were analyzed. One study found rinsing with 0.05% of NaF twice daily resulted in lower coronal caries increment. Another study reported the use of 1,100 ppm of NaF dentifrice twice daily showed lower percentage of coronal and root caries. A reduction of root caries was observed from using 5,000 ppm fluoridated toothpaste twice daily, annual professional 38% SDF solution application, six-monthly professional cleaning and APF gel application. The use of 0.12% CHX rinse and xylitol chewing gum did not show reduction of caries incidence. Toothbrushing with 5,000 ppm of NaF dentifrice, rinsing with 0.05% NaF, professional application of 38% SDF solution and APF gel may be effective at preventing caries among the elders.